2019
DOI: 10.1039/c9se00072k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-surface-area nitrogen-doped hierarchically porous carbon materials derived from chitosan and betaine hydrochloride sustainable precursors for high-performance supercapacitors

Abstract: A biobased polyelectrolyte was prepared and used successfully as a precursor for the fabrication of N-doped hierarchically porous carbon materials with tunable electrochemical properties in supercapacitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 54 publications
2
15
1
Order By: Relevance
“…This is similar to the highest SSA reported in one study, which was obtained from 400 C pyrolysis and activation at 800 C aer 100% KOH soaking. 42 However, most studies in the literature reported a maximum SSA athighertemperaturessuchas700, 43 800 44,45 or 900 C. 46,47 The discrepancy of our data may be explained by the 2-step process (pyrolysis and then activation) employed in this study as opposed to the 1-step process (simultaneous pyrolysis and activation) used in the literature. In the 1-step process, higher SSA results from the higher weight loss at higher temperatures, as observed from the pyrolysis in this study (Table S1 †).…”
Section: Resultscontrasting
confidence: 79%
“…This is similar to the highest SSA reported in one study, which was obtained from 400 C pyrolysis and activation at 800 C aer 100% KOH soaking. 42 However, most studies in the literature reported a maximum SSA athighertemperaturessuchas700, 43 800 44,45 or 900 C. 46,47 The discrepancy of our data may be explained by the 2-step process (pyrolysis and then activation) employed in this study as opposed to the 1-step process (simultaneous pyrolysis and activation) used in the literature. In the 1-step process, higher SSA results from the higher weight loss at higher temperatures, as observed from the pyrolysis in this study (Table S1 †).…”
Section: Resultscontrasting
confidence: 79%
“…However, at higher K 2 CO 3 /chitosan ratios, the surface area decreased. The average pore diameters and BET surface areas of the series of C-PAC750 materials were similar to those reported in the literature [23,24]. These results demonstrate that the introduction of the activator resulted in the generation of macro-, meso-, and micropores in the activated carbons accompanied by significant increases in the BET surface area.…”
Section: Chatacterization Of C-pac Samplessupporting
confidence: 88%
“…In particular, chitosan, a biopolysaccharide composed primarily of 2-amino-2-deoxy-D-glucose units and derived from chitin in crustacean cells, insect exoskeletons, and fungus cell walls, is the second most abundant biopolymer after cellulose. Because chitosan is naturally rich in nitrogen and possesses specific acid-base properties, there are various reports on the preparation of carbon materials using chitosan as a carbon precursor [15][16][17][18][19][20][21][22][23]. Kucinska et al reported a practical method for converting chitosan into activated carbon by employing a Na 2 CO 3 solution as an activator agent, which gave a porous carbon with a low surface area (400 m 2 •g −1 ) [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,43,44 From the perspective of molecular design and taking the merits of both of using biomass and relatively cheap protic ionic liquids as precursors, we recently reported a facile and structure tunable preparation method of precursors for preparation of N-doped porous carbon materials, which exhibited ultrahigh surface area, high N-doping content and showed good supercapacitor performance. [45][46][47] It is well know that the preparation ionic liquids with various anions usually use halogen-based anion ionic liquids as precursors through anion exchange reaction with corresponding organic or inorganic salts, in association with the yielding of halogen inorganic salts. For example, the preparation of DBUbased ionic liquids with benzenesulfonate anions.…”
Section: Introductionmentioning
confidence: 99%